Association of height loss and cardiovascular disease: Data from a large Korean cohort - Moon, Jeonggeun; Oh, Pyung Chun; Lee, Kyounghoon; Jang, Ho-Jun; Kim, Tae-Hoon; Park, Sang-Don; Kwon, Sung Woo; Kong, Min Gyu; Suh, Jon; Kang, Woong Chol (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Height declines with age, and its degree differs among individuals. Despite epidemiologic evidence for the inverse relationship between adult height and cardiovascular disease (CVD) incidence, the clinical significance of height loss in CVD remains to be elucidated. Therefore, this study investigated the association between height loss and CVD incidence. Methods: In total, 127,573 Korean participants were enrolled; their heights were monitored from 2002 to 2011. The annual height loss (cm/year) was the difference between the first and last height measurements within the observation period divided by the number of years. The participants were classified as Group 1 (height loss: <0.3 cm/year; n=102,554), Group 2 (height loss: 0.3–<0.6 cm/year; n=17,324), or Group 3 (height loss: ≥0.6 cm/year; n=7,695). Results: The cumulative major adverse cardiac and cerebral event (MACCE: cardiac death, non-fatal myocardial infarction, and unplanned hospitalization for heart failure or stroke) incidence rate was 3.6% for Group 1, 4.5% for Group 2, and 5.2% for Group 3. Group 2 (hazard ratio [HR]=1.27, 95% confidence interval [CI]=1.17–1.37) and Group 3 (HR=1.46, 95% CI=1.32–1.62) had a significantly higher incidence of MACCE than Group 1. In the model adjusted for age, sex, comorbidities, income level, body mass index, smoking, and drinking status, the MACCE risk was higher in Group 2 (HR=1.11, 95% CI=1.07–1.20) and Group 3 (HR=1.25, 95% CI=1.13–1.39) than in Group 1. Conclusions: The degree of height loss was independently associated with CVD occurrences in the Korean population.